2005
DOI: 10.1080/07399330500301846
|View full text |Cite
|
Sign up to set email alerts
|

Health Status and Access to Health Care of Documented and Undocumented Immigrant Latino Women

Abstract: Immigrant Latino women represent about one fifth of the total Latino population; however, data on health status and access to care for this population is limited. Using secondary data, we used a cross-sectional study to examine sociodemographic, migration, health status, and access to health care characteristics of immigrant documented and undocumented Latino women in North Texas. Undocumented women were less likely to report having health insurance and a regular health care provider, and reported lower educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
11

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 16 publications
4
76
0
11
Order By: Relevance
“…16 The barriers and their effects are exacerbated by language barriers and lack of familiarity with the healthcare system as well as fear of being arrested and deported. A similar problem was reported by migrant women in Kanchanaburi in this study.…”
Section: Community Contextmentioning
confidence: 99%
“…16 The barriers and their effects are exacerbated by language barriers and lack of familiarity with the healthcare system as well as fear of being arrested and deported. A similar problem was reported by migrant women in Kanchanaburi in this study.…”
Section: Community Contextmentioning
confidence: 99%
“…Further, unpredictable or seasonal work may lead to highly variable and unpredictable financial security which may promote food insecurity and hunger. Finally, low levels of acculturation may influence one's ability to access social services, influence shopping practices, and may promote remitting which may further undercut financial security 17 . The objectives of the present study were therefore to: (1) estimate the prevalence of hunger in a sample of undocumented Mexican migrants; (2) examine the extent to which social, economic and cultural variables are associated with the experience of hunger; and (3) assess whether hunger is associated with poor health.…”
mentioning
confidence: 99%
“…Other studies have reported that immigrant women often experience lower levels of education, precarious employment and irregular administrative status, which have been identified as barriers in accessing health care services (Grieco 2002;Marshall et al 2005). In addition, gender inequalities related to social roles and cultural norms may limit women's access to health care (Lane and Cibula 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to assess women's perceptions and perceived needs concerning health care to better understand the challenges they face in accessing and using health care services. Research on access and utilization of health care services of immigrants has based mainly on quantitative data (Dias et al 2008;Marshall et al 2005;Stronks et al 2001); lack of information on women's perspectives on these issues remains.…”
Section: Introductionmentioning
confidence: 99%